Effect of the Supporting Electrolyte on Chloroform Reduction at a Silver Electrode in Aqueous Solutions - Brudzisz, Anna M. (Molecules, 2021)
Herein, we report, for the first time, a comparative study on the electrocatalytic reduction of chloroform on silver in different aqueous supporting electrolytes. Cyclic voltammetry measurements were performed at a wide range of scan rates and concentrations of CHCl(3) using 0.05 M NaClO(4), NaH(2)PO4, and Na(2)HPO(4) as supporting electrolytes. We observed that a type of supporting electrolyte anion strongly influences both the potential as well as the current density of the chloroform reduction peak, mainly due to the presence of OH(−) in an alkaline Na(2)HPO(4) solution, which is a specifically interacting anion. Moreover, the highest sensitivity of the Ag electrode toward CHCl(3) reduction was observed in a neutral NaClO(4) aqueous solution. It was found that the electroreduction of chloroform at the silver surface occurs via a concerted mechanism regardless of the type of the studied supporting electrolyte.